2014
DOI: 10.3390/ijerph110403493
|View full text |Cite
|
Sign up to set email alerts
|

Clinically-Important Brain Injury and CT Findings in Pediatric Mild Traumatic Brain Injuries: A Prospective Study in a Chinese Reference Hospital

Abstract: This study investigated injury patterns and the use of computed tomography (CT) among Chinese children with mild traumatic brain injury (MTBI). We enrolled children with MTBI who were treated within 24 hours of head trauma in the emergency department of Wuhan Medical Care Center for Women and Children in Wuhan, China. Characteristics of MTBIs were analyzed by age and gender. Results of cranial CT scan and clinically-important brain injury (ciTBI) for children were obtained. The definition of ciTBI was: death f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…In the present study, boys outnumbered girls in pediatric TBI requiring hospitalization (male : female ratio, 1.6:1), which is consistent with previous studies on the ratio of TBI in boys and girls . The male : female ratios found by Shao et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, boys outnumbered girls in pediatric TBI requiring hospitalization (male : female ratio, 1.6:1), which is consistent with previous studies on the ratio of TBI in boys and girls . The male : female ratios found by Shao et al .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, boys outnumbered girls in pediatric TBI requiring hospitalization (male : female ratio, 1.6:1), which is consistent with previous studies on the ratio of TBI in boys and girls. 17,18,20,22,23,30,31 The male : female ratios found by Shao et al and Li et al were 1.87:1 and 2.28:1, respectively. 22 The higher proportion of boys being hospitalized for TBI may be related to previous findings that boys are naturally more active and adventurous than girls.…”
Section: Discussionmentioning
confidence: 88%
“…The systematic review to describe TBI epidemiology and to quantify TBI MOI yielded more than 240 full-text articles from an initial 8756 titles. [261][262][263][264][265][266][267] The search process is illustrated in detail in Fig. 3, while the full account of included articles with relevant epidemiological data is listed in Supplemental Table S2.…”
Section: Traumatic Brain Injury Moi and Injury Severitymentioning
confidence: 99%
“…20,21 Zhu et al showed that minor head trauma in boys is likely more common than in girls [69.2% vs. 30.8% of total mild TBIs (MTBIs) cases]. 22 A similar report from Peloso et al showed that head injury with symptoms of concussion is twice more in boys than girls. 23 Willer et al also reported the same result in which boys suffer an MTBI more likely than girls.…”
mentioning
confidence: 99%
“…Unlike these findings in another study by Zhu et al, they reported that 96.9% of children with minor head trauma were evaluated with CT scan, and 33.3% had abnormal CT findings. 22 In minor head trauma, which constitutes about 90.0% of children with head trauma, the management of these patients is not easy, and there are no widely accepted, evidence-based guidelines. 2,3, [17][18][19] It is important to identify predicating factors that could predict TBI that may help us to decrease unnecessary CT Scans.…”
mentioning
confidence: 99%